Correlation of Motivational Beliefs and Cognitive and Metacognitive Strategies with Academic Achievement of Students of Shiraz University of Medical Sciences - Ali Asghar Hayat; Majid Amiri Gharghani; Ahad Amiri Gharghani (Kerman University of Medical Sciences, 2018)
Background Success and academic achievement are among the most important goals of both students and educational systems. Researchers have examined the impact of different factors such as intelligence, personality, attitude, study habits, thinking skills and academic motivation on students' academic performance. Objectives The purpose of this study was to investigate the relationship of motivational beliefs and cognitive and metacognitive strategies with students' academic achievement. Methods In this descriptive - analytic cross-sectional study, the statistical population included all medical and health students of Shiraz University of Medical Sciences (1405 students), 250 of whom were selected according to the Levy and Lemeshow's formula. After estimating the sample size, the stratified random sampling method was used. To collect data, Pintrich and de Groot's motivated strategies for learning questionnaire (MSLQ) was employed. Data were analyzed using descriptive statistics, Pearson's correlation and independent -test. Results Among the components of cognitive learning strategies, comprehension (r = 0.1266, P < 0.10), and among the components of metacognitive learning strategies, the regulation component (r = 0.049, P < 0.05) had a significant positive correlation with academic performance. Among the components of motivational beliefs, the self-efficacy component (r = 0.173, P < 0.10) showed a significant positive correlation with academic performance. Based on the results of multiple regression analysis, only metacognitive learning strategies had the ability to predict the academic performance of the students. There was no significant difference between male and female students in any of the studied variables. Conclusions Based on the results, students who use more diverse cognitive strategies show better performance than others. Performance is more desirable among those who evaluate their understanding of the content of the course and make more efforts and have more perseverance (regulation) in the learning process. Students who believe in their abilities (self-efficacy) and reinforce these beliefs will have a better academic performance.